2005
DOI: 10.1172/jci24756
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting statistical power in the detection of genetic association

Abstract: The mapping of disease genes to specific loci has received a great deal of attention in the last decade, and many advances in therapeutics have resulted. Here we review family-based and population-based methods for association analysis. We define the factors that determine statistical power and show how study design and analysis should be designed to maximize the probability of localizing disease genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
99
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(103 citation statements)
references
References 108 publications
3
99
1
Order By: Relevance
“…Unlike association studies that evaluate presence of a certain allele or a genotype and presence of a disease 24 , we investigated these sites as potential predictors of time to onset of aseptic loosening after THA. Each SNP (site) was assessed with adjustment for the effects of other SNPs and with adjustment for sex, age at surgery and reason for THA 2,7,9 .…”
Section: Discussionmentioning
confidence: 99%
“…Unlike association studies that evaluate presence of a certain allele or a genotype and presence of a disease 24 , we investigated these sites as potential predictors of time to onset of aseptic loosening after THA. Each SNP (site) was assessed with adjustment for the effects of other SNPs and with adjustment for sex, age at surgery and reason for THA 2,7,9 .…”
Section: Discussionmentioning
confidence: 99%
“…Power to detect SNPs of small effect across multiple populations is further limited by constraints on trial design. Population sizes of many thousands have been recommended from simulation experiments to be necessary to detect associations in trees (Purcell et al 2003;Ball 2005;Gordon and Finch 2005), and human studies employing large populations commonly detect SNPs with small effects (,2%). Phenotypic variation arising from di- verse gene-by-environment interactions within and between sites was not accounted for in this study, whereas the discovery (Snowy Mountain Range) and validation (coastal valley in Southern Victoria) trials are strongly contrasted with respect to altitude, evapotranspiration, temperature, and soil type (New LocClim V 1.10).…”
Section: ; Dalla-salda Et Al 2009mentioning
confidence: 99%
“…Despite the potential promised from association genetics, several factors have been identified that influence power to detect true associations (Long and Langley 1999;Neale and Savolainen 2004;Gordon and Finch 2005;Newton-Cheh and Hirschhorn 2005). These factors can often be accounted for at the experimental design phase, by considering the extent of genome-wide LD, the candidate genes selected, the effect size, the number of genes affecting the trait, allele frequency, sample size, and rates of genotyping and phenotyping error.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 A widely used statistical method to assess association is the 2 test of independence, which assumes the null hypothesis of no association between the disease trait and a marker locus, most frequently at a 5% type I error rate. 25 Thus, if the P value corresponding to the 2 statistic is considered significant, the null hypothesis is rejected and an association is surmised. Depending on the marker being tested (often a SNP within a gene), the detected association could directly affect the phenotype (i.e., susceptibility variant) or may be linked to the true phenotypic effector.…”
Section: Genomic Study Of Complex Traitsmentioning
confidence: 99%